MAGNETIC ANOMALIES IN THE INTERIOR OF WESTERN SIBERIA AS POSSIBLE INDICATIONS OF ANCIENT SPREADING - Aplonov S.V. (My University, 1990)
This paper presents a detailed analysis of the data from a high-accuracy large-scale aeromagnetic survey of interior areas of Western Siberia where geological and geophysical data suggests the presence of oceanic lithosphere embedded in the basement. The first stage of the present work involved the two-dimensional autocorrelation and one-dimensional spectral analysis of the field measured during the above-cited 1:50,000 aeromagnetic survey. In the second stage, the magnetic fields in certain areas were subjected to adaptive energy filtering to extract the medium-period component that produces the distinctive characteristics (linearity and periodicity) of the overall field. Results confirm the presence of blocks of typical oceanic lithosphere (embedded) in the basement within the interior of Western Siberia and overlain by thick platformal sedimentary sequences and, in addition, demonstrate that linear anomalies marking ancient sea-floor spreading can be detected amid the overall continental magnetic field.